Slow Rockets and Fast Feathers or the Link between Exchange Rates and Exports : A Case Study for Pakistan - Brun, Martin; Gambetta, Juan Pedro; Varela, Gonzalo J. (World Bank, Washington, DC, 2020)
Export responses to real exchange rate (RER) depreciations in Pakistan are lower than those to appreciations. This paper empirically documents this asymmetric response using macro-level data. It then relies on a disaggregated export product–level data set for 2003–17 to test, within a panel fixed-effects framework, three hypotheses explaining the low export response to depreciations, focusing on information costs, supply constraints, and pricing to market. The analysis finds that (i) exports of differentiated products grow more slowly when the RER depreciates than they fall when it appreciates; (ii) exports from sectors with relatively greater supply constraints—in particular related to accessing finance- respond less to depreciations than to appreciations; and (iii) dollar prices for Pakistani exports tend to fall after nominal depreciations of the Pakistani rupee, in violation of the Dominant Currency Paradigm and consistent with pricing-to-market behavior, further accounting for the low response of exports to RER depreciations.